PERAN GURU DALAM MANAJEMEN KELAS TERHADAP PENINGKATAN MOTIVASI BELAJAR SISWA KELAS III SDN 4 MARGAWATI - Sofa Nurbani; Karantiano S. Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the role of teachers in classroom management in improving the learning motivation of third-grade students at SDN 4 Margawati. This research employed a qualitative approach with a descriptive research design. The subjects of this study were the third-grade teacher and students. Data were collected through observation, interviews, and documentation. The results indicate that the teacher’s role in classroom management includes organizing the learning environment, arranging seating, applying varied teaching methods, and providing reinforcement and motivation to students. Effective classroom management creates a conducive learning atmosphere, increases student engagement, and enhances learning motivation. Therefore, the teacher’s role in classroom management has a significant contribution to improving students’ learning motivation.